Tea Production in PT TAMBI Wonosobo - , YULIA RAMADIKA W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to provide information about PT Perkebunan Teh Tambi that focused on the tea production and tea classification in UP Tambi. The information are obtained from interview and library research by reading literature about tea production process. Based on the qualitative method, this paper explains the history of the company, tea production process that starts from plucking until packaging products, and tea classification. The conclusion of this paper is the production process in UP Tambi uses orthodox rotorvane system. Those systems consist of withering, rolling, grinding, wet sorting, enzymatic oxidation, drying, dry sorting, and packaging. After that, the tea will be classified in dry sorting process in grading room. Then, the tea will be tested by the tester in testing room. Tea that has good quality has strong aroma, the colors is dark, the size is homogen, its clean from any dust and fiber, and the steeping is bright.